2015
DOI: 10.1075/resla.28.1.07lar
|View full text |Cite
|
Sign up to set email alerts
|

El aprendizaje cultural en la enseñanza del inglés y su alcance en los libros de texto

Abstract: This paper analyses three B1-level textbooks used in EFL in Spain to gather information about how culture is taught, given that language learning and culture learning are closely related. A model of culture learning based on previous work by Paige, Jorstad, Paulson, Klein, and Colby (1999) and Lee (2009) has been designed in order to examine the textbooks’ cultural content. This functional framework gathers every theme and aspect of culture needed to develop each of the competencies that are required to accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Learners need to acquire knowledge about the target language community to later reflect on their own culture (McKay 2002: 83). This has led to a discussion among language teaching researchers regarding the new student training needs (Baker 2012;Byram 2008;Kramsch 1993;Larrea-Espinar 2015;Mendez-García 2005;Risager 2011). In order to communicate interculturally, apart from knowledge, students need to develop skills and attitudes (Byram 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Learners need to acquire knowledge about the target language community to later reflect on their own culture (McKay 2002: 83). This has led to a discussion among language teaching researchers regarding the new student training needs (Baker 2012;Byram 2008;Kramsch 1993;Larrea-Espinar 2015;Mendez-García 2005;Risager 2011). In order to communicate interculturally, apart from knowledge, students need to develop skills and attitudes (Byram 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Lee (2009) reported that high-school conversation textbooks in Korea neglected both the teaching of the culture-general aspect of culture learning and the small "c" target-culture learning. Likewise, Larrea-Espinar (2015) and Raigón-Rodríguez (2015) found that the small "c" aspect of culture was the most neglected in Spanish B1 and B2-level textbooks. Zarei and Khalessi (2011) reveal in their study of the Interchange Series in Iran that textbooks are culturally biased.…”
Section: Culture In Textbooksmentioning
confidence: 98%
“…In relation to methodology, one of the main approaches is content analysis. Thus, for example, Lee (2009), Larrea-Espinar (2015) and Raigón-Rodríguez (2015) used a cultural analysis table with different categories for each aspect of culture (culture in general, big "C" and small "c"). Yuen (2011) established four aspects to categorise foreign cultural references: products, practices, perspectives, and persons.…”
Section: Culture In Textbooksmentioning
confidence: 99%
See 1 more Smart Citation
“…The second part of this paper gathers a list of sitcom episodes that can be used in the EFL classroom to provide students with specific opportunities for cultural learning. To that aim, we have used a content checklist to identify cultural categories and themes in sitcoms (Lee, 2009;Larrea-Espinar, 2015). In that way, we have been able to determine and classify the type of cultural content and the topics in the sample episodes presented in Table 2.…”
Section: -Suggested Sitcom Episodes For Cultural Learningmentioning
confidence: 99%